Implementation of a Novel Structured Social and Wellness Committee in a Surgical Residency Program: A Case Study - Van Orden, Kathryn E.; Talutis, Stephanie D.; Ng-Glazier, Joanna H.; Richman, Aaron P.; Pennington, Elliot C.; Janeway, Megan G.; Kauffman, Douglas F.; Dechert, Tracey A. (Frontiers in Surgery, 2017)
This article provides a theoretical and and practical rational for the implementation of an innovative and comprehensive social wellness program in a surgical residency program at a large safety net hospital on the East Coast of the United States. Using basic needs theory, we describe why it is particularly important for surgical residency programs to consider the residents sense of competence, autonomy, and belonging during residence. We describe how we have developed a comprehensive program to address our residents' (and residents' families) psychological needs for competence, autonomy, and belongingness.